The Effect of Hormonal Status on the Results of Aromatase Inhibitor Maintenance Following Adjuvant Chemotherapy for High-Grade Serous Ovarian Cancer (HGSOC) - Bibi Sajida, Huma Aslam, Nosheen, Bushra Rashid, Ayesha Samad Dogar, Nargis Gulab, Rakhshinda Inam Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The prognosis of epithelial ovarian cancer (EOC) depends on the patient’s receptor status, which is influenced by hormones. Although there is conflicting evidence about the predictive power of molecular targets such as ER and PgR for tumor response, hormone therapy has the potential to aid patients with advanced EOC. Objective: The purpose of this study was to analyze the relationship between hormonal status and the success of aromatase inhibitor maintenance after adjuvant chemotherapy for HGSOC. Method: This study was conducted at the department of Gynae and Obs, DHQ hospital, KDA, Kohat during June 2022 to June 2023. One hundred and ten patients participated in this prospective clinical trial to see how well and safely aromatase inhibitor (AI) maintenance endocrine therapy with 2.5 mg of letrozole daily, given off-label, worked. Patients were treated for a maximum of five years, or until side effects, symptomatic recurrence, or the need for more chemotherapy became apparent. Immunohistochemistry was used to evaluate correlations with ER and PgR. SPSS 22.0 was used to analyze all data. Results: The included had mean age 53.12 years and had mean BMI 31.54 kg/m2. Frequency of postmenopausal was higher found in 70 (63.6%) as compared to premenopausal cases 40 (33.6%). Most common symptoms was abdominal pain found in 93 (84.5%) cases. Rate of relapse was found in 46 (41.8%) cases. 26 cases of relapsed disease and 35 cases of non-relapsed received aromatase inhibitorn (AI) maintenance. However, when looking at disease-free survival and relapse rates together, no significant differences were seen. Conclusion: Our data do not support aromatase inhibitor maintenance therapy for HGSOC. AIs are appealing due to their low cost and safety, but our group’s lack of significant improvement in RR or DFS suggests more targeted and customized treatment. Keywords: HGSOC, aromatase inhibitor, disease free survival, Symptoms